Pembentukan Konsep Diri dan Tindakan Labeling pada Remaja - Nurannisa Sawitri; Ati Kusmawati (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
Labeling in adolescents can be formed from a deviation that occurs due to a negative gap in their social environment, which affects their behavior and lifestyle. Islamic Junior High School are not differentiated from other public schools because adolescents always want to try new things to find their identity. In addition, the formation of self-concept is also obtained from the process of interaction with the social environment with the suitability between self-image and ideal self. This study aims to see the relationship between self-concept formation and labeling actions in adolescents, so this research is quantitative correlation with data collection using a questionnaire. The results obtained from this study show that there is an act of labeling in schools with Islamic values and the formation of self-concept in adolescents can be influenced by the act of labeling with a positive and significant value. Adolescents who are socially labeled will see themselves as the label given by their environment.